2018
DOI: 10.7577/seminar.2978
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation in Swedish schools – Principals’ strategic leadership and organisation of tablet-based one-to-one computing initiatives

Abstract: This paper reports on a research study about principals’ strategic leadership and organisation of schools within established tablet-based one-to-one computing initiatives. The aim was to investigate how principals lead and guide one-to-one computing initiatives in K–12 education. The research questions focused on principals’ expressed intentions and their strategic leadership and organisation when implementing tablet-based one-to-one computing initiatives in Swedish schools. The empirical material was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Despite the urgent national and global demands mentioned above, Swedish schools show a limited focus on developing these competencies, even though large-scale oneto-one computing initiatives have been implemented in recent years [31] [32]. Mårell-Olsson and Bergström [33] found principals to argue that their motives for the one-toone computing initiatives are to provide a potential opportunity for organisational change and that their primary focus and endeavour is to improve their school's rankings because doing so brings advantageous financial effects. In the study, the researchers showed that the principals were, so to speak, setting the scene for the oneto-one computing initiatives and were laying the foundation for the teachers' work with digital technologies [33].…”
Section: The Swedish School Context and Digitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the urgent national and global demands mentioned above, Swedish schools show a limited focus on developing these competencies, even though large-scale oneto-one computing initiatives have been implemented in recent years [31] [32]. Mårell-Olsson and Bergström [33] found principals to argue that their motives for the one-toone computing initiatives are to provide a potential opportunity for organisational change and that their primary focus and endeavour is to improve their school's rankings because doing so brings advantageous financial effects. In the study, the researchers showed that the principals were, so to speak, setting the scene for the oneto-one computing initiatives and were laying the foundation for the teachers' work with digital technologies [33].…”
Section: The Swedish School Context and Digitalizationmentioning
confidence: 99%
“…Mårell-Olsson and Bergström [33] found principals to argue that their motives for the one-toone computing initiatives are to provide a potential opportunity for organisational change and that their primary focus and endeavour is to improve their school's rankings because doing so brings advantageous financial effects. In the study, the researchers showed that the principals were, so to speak, setting the scene for the oneto-one computing initiatives and were laying the foundation for the teachers' work with digital technologies [33]. The curriculum becomes an important part of the teaching design when teaching practices are digitalised and teachers begin to exclude textbooks and instead include an array of both digital and physical learning resources [31].…”
Section: The Swedish School Context and Digitalizationmentioning
confidence: 99%
“…This framework has been used to study digitalization and leadership (Dexter, 2018;Petersen, 2014), goals and policies (Vanderlinde et al, 2012), and the roles of school leaders in digitalization (Håkansson-Lindqvist & Pettersson, 2019). From another perspective, Mårell-Olsson and Bergström (2018) conceptualized strategic school leadership as the awareness of goals and motives and the implementation of actions and strategies for organizing and leading processes of digital and educational change. Researchers have also studied the enactment of school leadership by analyzing microprocesses from historical and sociocultural perspectives (Vennebo, 2017 see also Hauge, 2016).…”
Section: Digitalization In Schools -Organization and Leadershipmentioning
confidence: 99%
“…one laptop or tablet per child) that have been implemented in compulsory schools. Despite these digitizing initiatives, research shows that teaching designs in Sweden [5][6] [7] [8] as well as in Denmark [9], are mostly organized through teacher-centered instructions which, to a limited extent, promote studentcentered learning activities aimed at the development of student abilities to collaborate, reason critically, communicate, solve complex problems and use digital tools in teaching and learning (e.g. 21st century skills).…”
Section: Introductionmentioning
confidence: 99%